2017
DOI: 10.1007/s10661-017-6356-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use types on dissolved trace metal concentrations in the Le’an River Basin, China

Abstract: Using land use types in multiple spatial scales (entire basin, buffer zones, and slopes) as well as statistical and spatial analysis, relationships between land use types and concentrations of dissolved trace metals were determined in the Le'an River Basin, China. The result showed that farmland and urban land were determined as the source of the pollutants, while forestland and grassland were identified as the sink of the pollutants. The temporal differences of relationships between land use types and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
0
12
0
10
Order By: Relevance
“… 1 SD: standard deviation; 2 CV: the coefficient of variation; 3 K-S test: the Kolmogorov-Smirnov (K-S) test; 4 nd: no data. Data sources: 5 Chinese Ministry of Health [45]; 6 WHO (the World Health Organization) [49]; 7 US EPA (the United States Environmental Protection Agency) [50]; 8 Li [46]; 9 Ribeiro et al [48]; 10 Zuzolo et al [19]; 11 Jiang et al [10]; 12 Wang [47]; 13 Li et al [9]; 14 Li and Zhang [16]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… 1 SD: standard deviation; 2 CV: the coefficient of variation; 3 K-S test: the Kolmogorov-Smirnov (K-S) test; 4 nd: no data. Data sources: 5 Chinese Ministry of Health [45]; 6 WHO (the World Health Organization) [49]; 7 US EPA (the United States Environmental Protection Agency) [50]; 8 Li [46]; 9 Ribeiro et al [48]; 10 Zuzolo et al [19]; 11 Jiang et al [10]; 12 Wang [47]; 13 Li et al [9]; 14 Li and Zhang [16]. …”
Section: Figurementioning
confidence: 99%
“…Globally, heavy metals are one of the most hazardous pollutants in water [1,2,3,4,5,6], and can be observed in dissolved phase [7,8,9,10], suspended particle phase [11,12,13], and sedimentary phases [14,15] in water systems. Dissolved heavy metals are generally more toxic than other phases [7,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heavy metals are difficult to be degraded or relieved of harmfulness through physical, chemical, or biological purification in natural environments [5], and can cause severe diseases, such as nervous disorders, visceral dysfunction, and cancers, through food chains [6,7]. Heavy metals in the dissolved phase are one of the most harmful substances that can directly affect the water quality of drinking water and irrigation water [8][9][10][11], and they are of greater toxicity than those in suspended and sedimentary phases [12][13][14]. In order to control water pollution and protect local water resources, it is of great significance to understand the spatial distribution, temporal variation, and sources of dissolved heavy metals, as well as the water quality and health risk level of water.…”
Section: Introductionmentioning
confidence: 99%
“…Different slopes are crucial spatial factors that detect the relationships between landscape types and water quality in water ecosystems. Yu et al (2016) found that landscape types on various slopes are helpful to identify the relationship between landscape patterns and water quality [23]. However, we still lack the information on the effects of different topographic characteristics upon the relationship between the concentration of trace elements and landscape patterns.…”
Section: Introductionmentioning
confidence: 99%